1994
DOI: 10.1007/bf02015446
|View full text |Cite
|
Sign up to set email alerts
|

Non-union of pediatric fibula fractures: Easy to overlook, painful to ignore

Abstract: Fracture non-union in the pediatric population may span the age range from childhood to adolescence. Fracture non-union in children and adolescents is often due to an underlying cause such as affliction with neurofibromatosis or osteogenesis imperfecta. Although less commonly seen, non-union may occur in the otherwise healthy pediatric population. We report three cases of fracture non-union of the distal end of the fibula in the pediatric age group. All three were characterized by persistent local pain and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The rate of fracture nonunion in the long bones of pediatric patients has been reported in several relatively large series and ranged from 0% to 1.7% (15). A few reports of nonunion of pediatric ankle fractures have been reported (16,17). Haramati et al (17) reported on 3 nonunions associated with distal fibular fractures.…”
Section: Discussionmentioning
confidence: 95%
“…The rate of fracture nonunion in the long bones of pediatric patients has been reported in several relatively large series and ranged from 0% to 1.7% (15). A few reports of nonunion of pediatric ankle fractures have been reported (16,17). Haramati et al (17) reported on 3 nonunions associated with distal fibular fractures.…”
Section: Discussionmentioning
confidence: 95%
“…8 Literature search showed four case reports describing nonunion following conservative treatment of closed paediatric fractures. 9 Two involved distal ulna, one distal radius and one distal fibula. In a series of thirty cases of diaphyseal nonunion in children reported by Lewallen et al, only two cases were closed fractures treated by closed means, both involving tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture non-union in the pediatric population can occur from childhood to adolescence, and is often due to underlying causes such as neurofibromatosis or osteogenesis imperfecta. Although less commonly seen, non-union may also occur in the otherwise healthy pediatric population ( 31 ).…”
Section: Discussionmentioning
confidence: 99%